PERAN ORANG TUA TERHADAP PENINGKATAN PRESTASI BELAJAR ANAK DI DESA UMAUTA - KECAMATAN BOLA KABUPATEN SIKKA - Rospita Sate; Khidir, Khidir; Rodja Abdul Natsir (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Education is a necessity for a person and is carried out indefinitely. Education can be obtained through formal and non-formal education. As parents, their roles and responsibilities are absolute. But not all parents understand that children's education is important in laying the basis for thinking and understanding of life. There are parents who think that education is the responsibility of the educator namely the school. The purpose of this study was to find out about the role of parents in improving children's learning achievement in Umauta Village, Bola District, Sikka Regency. This research uses a qualitative approach. The subjects in this study were parents, numbering 8 people and all of them were studied. Data collection uses observation, interview, and documentation techniques. From the data obtained and then analyzed, the results of this study indicate that, in improving children's learning achievement, it is very necessary the role of parents in terms of caring for, educating, supporting, and motivating children because of the participation of parents, there is progress and improvement in learning achievement children can continue to improve. The role played by parents in the Desa Umauta towards improving children's learning achievement is already good. This can be seen from the various efforts made by parents so that their children's performance always increases. The role of parents in determining children's learning achievement is very large